2008
DOI: 10.1007/s11032-008-9241-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of regeneration procedures on the genetic integrity of Brassica oleracea accessions

Abstract: A Brassica oleracea collection of landraces collected in the northwest of Spain is kept at the Gene Bank placed at 'Misión Biológica de Galicia'. Landraces of the collection are regenerated from time to time to restore the viability of the seed and to carry on field trials. The objective of this work is to study the effect of regeneration on the genetic integrity of three accessions of this collection, and to investigate the possible causes of the genetic changes observed. After characterizing the original pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…When Börner et al (2000) studied, with the help of microsatellite markers, the genetic identity of wheat accessions regenerated up to 24-times, genetic drift was observed in one out of eight wheat accession. Changes in allele frequencies due to the action of genetic drift, directional selection and assortative mating were detected also by Le Clerc et al (2003), van Hintum et al (2007) and Soengas et al (2009), who studied the effect of regeneration procedures on the integrity of several opencrossing species. Recently, the study of open-crossing Brassica oleracea L. landraces showed significant changes in the allele frequency of individual loci even after only two regeneration cycles (Soengas et al 2009).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…When Börner et al (2000) studied, with the help of microsatellite markers, the genetic identity of wheat accessions regenerated up to 24-times, genetic drift was observed in one out of eight wheat accession. Changes in allele frequencies due to the action of genetic drift, directional selection and assortative mating were detected also by Le Clerc et al (2003), van Hintum et al (2007) and Soengas et al (2009), who studied the effect of regeneration procedures on the integrity of several opencrossing species. Recently, the study of open-crossing Brassica oleracea L. landraces showed significant changes in the allele frequency of individual loci even after only two regeneration cycles (Soengas et al 2009).…”
Section: Discussionmentioning
confidence: 65%
“…Changes in allele frequencies due to the action of genetic drift, directional selection and assortative mating were detected also by Le Clerc et al (2003), van Hintum et al (2007) and Soengas et al (2009), who studied the effect of regeneration procedures on the integrity of several opencrossing species. Recently, the study of open-crossing Brassica oleracea L. landraces showed significant changes in the allele frequency of individual loci even after only two regeneration cycles (Soengas et al 2009). Similarly to our data, Parzies et al (2000) observed significant decline in the average gene diversity and allele number per locus over the time of barley landraces conserved for different time.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Only a few investigation of the genetic integrity have been performed on long-term conserved accessions undergoing periodical regeneration and changes in allelic frequencies were detected in various species (Enjalbert et al 1999;Parzies et al 2000;Le Clerc et al 2003;van Hintum et al 2007;Smýkal et al 2008;Soengas et al 2009;Cieslarová et al 2011). These findings imply that regeneration protocols should be improved to accommodate more numerous samples (larger population, Ne) and the composition of the collection should be continuously monitored to prevent the risk of genetic diversity loss.…”
Section: Developing Global Conservation Strategiesmentioning
confidence: 99%
“…Much eff ort has been put into establishing ex situ collections representing landrace and wild relative diversity of cultivated crop species. Regardless of the level of intra-accession diversity, there have been relatively few empirical studies that directly examine the impact of ex situ conservation procedures on genetic variation (Parzies et al, 2000;Börner et al, 2000;Chebotar et al, 2003;Van Hintum et al, 2007;Soengas et al, 2009;Hirano et al, 2009). Trade-off s typically can be viewed as a logistic limitation (increasing regeneration sizes) vs. a quality limitation (loss of genetic diversity).…”
mentioning
confidence: 99%